Postcards from the EDge project: randomised controlled trial of an intervention using postcards to reduce repetition of hospital treated deliberate self poisoning. Issue 7520 (23rd September 2005) - Carter, Gregory L; Clover, Kerrie; Whyte, Ian M; Dawson, Andrew H; Este, Catherine D
Abstract : Abstract: Objective To determine whether an intervention using postcards (postcards from the EDge project) reduces repetitions of hospital treated deliberate self poisoning. Design Randomised controlled trial. Setting Regional referral service for general hospital treated deliberate self poisoning in Newcastle, Australia. Participants 772 patients aged over 16 years with deliberate self poisoning. Intervention Non-obligatory intervention using eight postcards over 12 months along with standard treatment compared with standard treatment alone. Main outcome measures Proportion of patients with one or more repeat episodes of deliberate self poisoning and the number of repeat episodes for deliberate self poisoning per person in 12 months. Results The proportion of repeaters with deliberate self poisoning in the intervention group did not differ significantly from that in the control group (57/378, 15.1%, 95% confidence interval 11.5% to 18.7% v 68/394, 17.3%, 13.5% to 21.0%: difference between groups -2%, -7% to 3%). In unadjusted analysis the number of repetitions were significantly reduced (incidence risk ratio 0.55, 0.35 to 0.87). Conclusion A postcard intervention reduced repetitions of deliberate self poisoning, although it did not significantly reduce the proportion of individual repeaters.